Problematizando la categoría “sujeto del Derecho”: un análisis antirracista de la evolución de los derechos humanos y de la naturaleza (Tema Central) - Nwadiaru Moreira, Lois Adamma (2025)
This article analyses, from an anti-racist perspective, the evolution of human and nature rights in Ecuador. Using the historical-logical qualitative method, documentary analysis as a technique for data collection and analysis and an anti-racist methodological approach, it is revealed how legal norms and practices have perpetuated historical ethnoracial inequalities in this country. In addition, it explores the current state of human and nature rights in relation to the Afrodescendant population in Ecuador, highlighting the biocentric worldview of this population, as opposed to the extractive practices of Ecuador’s production model. Finally, it suggests the need to restructure regulations to address the roots of these inequalities, promoting a restorative approach that guarantees the collective rights of Afro-descendant populations.